Algorithm-Aided Diagnosis of Chronic Pulmonary Aspergillosis in Low- And Middle-Income Countries by Use of a Lateral Flow Device - Kwizera, Richard; Katende, Andrew; Teu, Anneth; Apolot, Denise; Worodria, William; Kirenga, Bruce J.; Bongomin, Felix (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
Chronic pulmonary aspergillosis (CPA) is a slowly progressive parenchymal lung disease typically caused by Aspergillus fumigatus. CPA affects immunocompetent or subtly immunocompromised patients with underlying structural lung diseases and is estimated to affect approximately three million people per year worldwide. It can co-exist with pulmonary tuberculosis (PTB), has both pulmonary and systemic symptoms that are clinically indistinguishable from that of PTB, and is often misdiagnosed and managed as smear-negative PTB. According to the Infectious Diseases Society of America (IDSA), the European Society for Clinical Microbiology and Infectious Diseases (ESCMID), the European Confederation of Medical Mycology (ECMM), and the European Respiratory Society (ERS) Guidelines, the diagnosis of CPA should be based on characteristic symptoms and radiologic features present or presumed to have been present for at least 3 months in a patient with no or minimal immunosuppression and a prior or current lung condition with microbiological or immunological evidence of Aspergillus spp. infection. This definition is consistent with the original definition of CPA proposed by Denning and colleagues . Still, CPA is under- and mis-diagnosed in resource-constrained settings where adequate diagnostics are unavailable. Previously treated PTB is the most common risk factor for the development of CPA even in the developed world . The global burden of CPA attributed to healed TB lesions alone has been estimated to over 1.2 million cases annually globally. On the other hand, active PTB is the number one differential diagnosis for CPA and CPA is the number one differential diagnosis for patients previously treated for microbiologically confirmed PTB who are currently sputum smear-negative. Recent evidence has shown that the annual rate of new CPA development following completion of PTB treatment is about 6.5% in those with chest radiography cavitation and 0.2% in those without.